A comparison of findings on parents' and teachers' questionnaires, and detailed ophthalmic and psychological assessments. Issue 9 (20th August 2004) - O'Connor, A R; Stephenson, T J; Johnson, A; Wright, S D; Tobin, M J; Ratib, S; Fielder, A R
Abstract : Background: Questionnaires are important tools used to gain information about health and level of function in different domains. Aims and Methods: To determine the degree of agreement between questionnaires, administered to parents and teachers, and ophthalmic and psychological examinations in a cohort of 309 low birth weight children (<1701 g) at age 10–13 years. Results: A total of 90.9% of cases showed agreement between the question on distance vision and clinical assessment, and agreement for the near vision question was 83%. However, the correlation on an individual basis was only fair (kappa = 0.46, distance vision) to poor (kappa = 0.2, near vision). The overall agreement for the questions on cognitive ability was better than the correlation, whereas the questions on reading and mathematical ability showed low agreement and low correlation. Conclusion: Questionnaire assessment of vision and cognitive ability is more suitable for studying the outcome of a large population than for identifying deficits in individuals.